Análise da proficiência motora e capacidade física de crianças e adolescentes asmáticos: estudo transversal - Luiz, Josiane Germano (2019)
INTRODUCTION: It is well established in the literature that asthma is one of the most common chronic respiratory diseases in childhood, and in addition to pulmonary limitations, it also has systemic repercussions and may reduce tolerance to physical activity. However, there is a lack of information on motor proficiency in asthmatic children and adolescents, which is one of the most important factors for physical activity performance at this stage of development. OBJECTIVE: To evaluate the physical and functional capacity of asthmatic children and adolescents, as well as evaluate the quality of life, body composition and verify the correlation between motor proficiency, respiratory and physical capacity, quality of life and body composition of asthmatic children and adolescents. METHODS: A cross-sectional study to be performed with asthmatic children and adolescents aged 4 to 16 years, allocated to Group A (Asthma) and Group B (Control), to be evaluated for motor proficiency with the Motor Assessment Assessment Battery for Children 2nd edition (MABC-2), incremental shuttle walk test, quality of life questionnaire and Asthma Control Questionnaire (ACQ6). RESULTS: Included 50 individuals who were not practicing physical activity, 25 asthmatics and 25 controls separated by 3 age groups from 4 to 6, 7 to 10 and 11 to 16 years. In the Asthma Group (AG) the average was 7.7±2,65 years and Control Group (CG) the average age was 10.9±3,89 years; both groups had poor ISWT performance, and AG had lower ISWT level, there was significant change in MABC-2 Aiming and Cathing (AC) domain, negative correlations between Manual Dexterity and Asthma control, and correlation between ISWT and Balance. CONCLUSION: This is the first study on the Motor Proficiency of asthmatic children and adolescents, in which the Grasping and Throwing domain has been reduced in asthmatics, and reduced physical capacity seems to influence motor proficiency.